LODGING FACILITY MANAGERS’S PERCEPTIONS OF ONLINE HOME-RENTAL PLATFORMS - Ferreira, Karolina Matias (2017)
Online home-rental platforms have increased rapidly, gaining a prominent position in recent years, because they represent an innovation in the provision of tourism services, and have had a negative effect on the results of traditional lodging businesses. In view of this scenario, the aim of this article was to investigate the perceptions of lodging facility managers on shared economy, collaborative consumption, and online home-rental platforms in five different cities in the State of Rio de Janeiro. As this was an exploratory study, a qualitative survey was conducted through semi-structured questionnaires, which were distributed via SurveyMonkey. The results indicate that businesses need to adapt to this new scenario: lodging services distributed across online platforms, at prices below those offered by the traditional market. It is noted that there is a need for these managers to create strategies of segmentation or marketing differentiation that would provide added value to their organizations and minimize the effects of this new market niche.